Multiple meanings of gender equality : a critical frame analysis of gender policies in Europe - Verloo, Mieke, 1950- (CPS Books., 2007)
This book aims to map the diversity of meanings of gender equality across Europe and reflects on the contested concept of gender equality. In its exploration of this diversity it not only takes into account the existence of different visions of gender equality and the way in which different political and theoretical debates crosscut these visions, but also reflects upon the geographical contexts in which visions and debates over gender equality are located. The contextual locations where the analyzed debates take place include the European Union and Austria, Greece, Hungary, the Netherlands, Slovenia, and Spain. In the discussion of the different ways of framing gender equality, each chapter provides insights into the ongoing theoretical and political debate about "what is gender equality?", disclosing the visions, debates, and contexts that move around and contribute to shape such a complex and contested concept.